DEVELOPMENT OF THE DOWN PASSING EXERCISE TOOL FUTSAL EXTRACURRICULAR JUNIOR HIGH SCHOOL STUDENTS - Sabarudddin Yunis Bangun; Raja Syaifullah Sihombing; Rafli Hadinata (Journal Physical Education, Health and Recreation, 2022)
The purpose of this study was to develop a tool for passing down training for junior high school students in extracurricular Futsal. The subjects in this study were extracurricular Futsal students at Harapan Mekar Middle School, Medan. The research instrument used was a questionnaire/questionnaire. The results of the development research data were obtained through expert evaluations and group trials through filling out questionnaires. The results of the material expert validators as a whole in Phase I obtained results of 86% and in Phase II obtained results of 90%. Categorized as "Eligible" and the results of the media validators as a whole in Phase I obtained results of 88% and Phase II obtained results of 86 % categorized as “Eligible”. The results of student questionnaires in the small group trial obtained results of 90.1% categorized as "Very Eligible" and the results of student questionnaires in the large group test obtained results of 88.8% categorized as "Eligible". The final assessment of this product as a whole is "Eligible" as a medium or a means to help under-passing practice for Futsal extracurricular junior high school studen